2019
DOI: 10.1093/aobpla/plz057
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultraviolet reflectance and pattern in the pollination system of Hypoxis camerooniana (Hypoxidaceae)

Abstract: Apart from floral morphology and colours perceived by the human eye, ultraviolet (UV) reflectance acts as an important visual advertisement of numerous flowering plant species for pollinators. However, the effect of UV signalling on attracting pollinators of particular plant species is still insufficiently studied, especially in the Afrotropics. Therefore, we studied the pollination system of Hypoxis camerooniana in montane grasslands of Mount Cameroon, West/Central Africa. We focused mainly on the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…On the other hand, even with an unclear colour preference, flies are usually related to yellowish flowers (Lunau, 2014), such as the (EC) fly-pollinated species registered in our study. The absence of UV reflectance does not discourage fly-pollination of the tropical Hypoxis camerooniana (Klomberg et al, 2019) but the presence of UV pattern favoured fly visitation of the temperate Argentina anserina flowers. Flies are sensitive to UV (Chittka and Briscoe, 2001;Cronin et al, 2014;Lunau, 2014) and maybe tuned to yellow UV-patterned flowers (An et al, 2018), similar to Cissus erosa, the fly-pollinated species sampled here.…”
Section: Floral Uv Features and Plant-pollinator Interactionmentioning
confidence: 92%
See 1 more Smart Citation
“…On the other hand, even with an unclear colour preference, flies are usually related to yellowish flowers (Lunau, 2014), such as the (EC) fly-pollinated species registered in our study. The absence of UV reflectance does not discourage fly-pollination of the tropical Hypoxis camerooniana (Klomberg et al, 2019) but the presence of UV pattern favoured fly visitation of the temperate Argentina anserina flowers. Flies are sensitive to UV (Chittka and Briscoe, 2001;Cronin et al, 2014;Lunau, 2014) and maybe tuned to yellow UV-patterned flowers (An et al, 2018), similar to Cissus erosa, the fly-pollinated species sampled here.…”
Section: Floral Uv Features and Plant-pollinator Interactionmentioning
confidence: 92%
“…In general, it has been shown that conspicuous flowers can receive more pollinator visits , which might represent selection pressures toward more contrasting and distinguished visual features. Indeed, floral UV-patterns may favour bee attraction (Rae and Vamosi, 2013;Klomberg et al, 2019) and may increase the probability of the pollinator reaching floral resources, reducing handling time (Dinkel and Lunau, 2001;Leonard and Papaj, 2011). In spite of the predominance of UV-patternless flowers in butterfly-, hummingbird-, beetle-, bat-, and hawkmothpollinated species, we cannot disregard the importance of UV patterns for these pollinators until there are experimental evidences.…”
Section: Floral Uv Features and Plant-pollinator Interactionmentioning
confidence: 99%
“…In addition to all this, bracts are also extremely important for attraction of pollinators in some species (Bertechine Gagliardi et al 2018), as might also be the case with H. epipactis (Bavcon 2013). In 25% of angiosperm flowers, the reflection of ultraviolet light represents an important visual information for pollinators (Klomberg et al 2019). Based on all this, we presumed that bracts might differ from basal leaves regarding their biochemical structure and optical properties, especially in the UV range.…”
Section: Introductionmentioning
confidence: 91%
“…The flowering plant species along the set transects were recorded for a 24-hour period using security cameras (VIVOTEK IB8367T with IR night vision; for more information on the methodology see Klomberg et al, 2019;Mertens et al, 2020Mertens et al, , 2018 to detect and identify flower visitors to 13 functional groups of pollinators. We recorded flowers at all vegetation strata from understory to canopies (reached using tree climbing methods).…”
Section: Visitor Recordingmentioning
confidence: 99%